Online HIV/STI Risk Test (ORT): A prospective cross‐sectional study among sexually active individuals in Germany. (26th February 2022) - Skaletz‐Rorowski, Adriane; Potthoff, Anja; Nambiar, Sandeep; Basilowski, Miriam; Wach, Janet; Kayser, Arne; Kasper, Andre; Brockmeyer, Norbert H.
Summary: Background: Our goal was to develop and evaluate an anonymous self‐administrable web‐based test to determine risk for HIV/STI. Methods: The Online HIV/STI Risk Test was developed and hosted since 12/2017. 11, 529 participants completed the test and 10, 668 were analyzed. The test included multiple choice questions about sociodemographic data, sexuality, sexual risk behavior, HIV/STI testing. Participant data was stratified by gender and sexuality and analyzed. Results: 84.5 % were aged 18–39, 7.5 % < 18 and 8.1 % > 40. Males were 53.1 %, female 46.3 % and trans 0.6 %. 12.5 % were men who have sex with men (MSM). 59.1 % and 66.0 % of participants were vaccinated for hepatitis A and B respectively, but 75.1 % unvaccinated for HPV. Prior and repeated instances of HIV or other STI were higher among MSM. Yet, 61.4 % females, 70 % males and 55.4 % MSM had never tested for an STI. Although prevalence of > 3 sexual partners in the last twelve months was highest among MSM, condomless sex was greater among women. 34.5 % of males, 25.6 % of females, and 75 % of MSM engaged in anal sex respectively. Conclusions: The online HIV/STI Risk Test is a useful tool to acquire data on STI risk‐behavior for strategizing STI prevention, testing, and vaccination, thus improving sexual health.